ANALISIS AKTIVITAS ANTIOKSIDAN DENGAN METODE DPPH SERTA TINGKAT PENERIMAAN KOPI ARABIKA KOYA - Asrul D. Irwinsyah; Jan R. Assa; Yoakhim Y.E Oessoe (Universitas Sam Ratulangi, 2022)
ABSTRACT Coffee is a commodity in the world that is cultivated by more than 50 countries and Indonesia ranks 4th in the world as the largest coffee producing country. Two coffee varieties that are generally known are Robusta and Arabica varieties. Coffee processing is very important in determining the quality and taste of coffee. The purpose of this study is to obtain antioxidant activity and likeness levels of Arabica coffee in Koya Village, North Sulawesi Province. The method used is descriptive method with the treatment of variations in temperature and roasting time. The results of the analysis for antioxidant activity ranged from 36.01 - 47.66% inhibition obtained with IC50 values between 41.44 - 93.37 Î¼g / ml. antioxidant properties with a very strong category in treatment B (temperature 180 â„ƒ with a roasting time of 30 minutes) and in treatment C (temperature 220 â„ƒ with a roasting time of 22 minutes). Testing the preferred level of Arabica coffee drinks which include the most preferred color, aroma and taste parameters in treatment C. Keywords: Arabica, temperature, roasting time